Food Safety Training Workshop. Theme: Managing food safety and quality in small-scale food processing for Roots, Tubers and Bananas (RTB) value chains in Sub-Saharan Africa. - Musyoka, J.; Njunge, F.; Muzhingi, T. (International Potato Center, 2018)
Managing food safety and quality in small-scale food processing for Roots, Tubers and Bananas (RTB) value chains in Sub-Sahara Africa training workshop took place on 4th - 8th of December 2017 at the International Livestock Research Institute in Kenya. The training was attended by 27 participants (15 men and 12 women) from 11 countries (Ethiopia, Kenya, Ghana, Nigeria, Uganda, Cameroon, Tanzania, DRC, Malawi, USA, and UK). They also came from various sectors including government, academia, private-sector (food processors), non-profit organizations and religious organizations. The objective of the training workshop was to enhance compliance to food safety regulations by small-scale enterprises involved in RTB processing in sub-Saharan Africa (SSA). The actors gained skills and knowledge from the training important in addressing food safety challenges that arise from lack of compliance to good Hygiene and Manufacturing Practices.